Kualitas Pelaporan Keuangan Pemerintah Daerah Ditinjau dari Sumber Daya Manusia, Pengendalian Intern, Pemanfaatan Teknologi Informasi (Studi Empiris Pada DPPKAD Pemerintah Kabupaten Klaten, Boyolali, Sukoharjo, dan Kota Surakarta) - Septiani, Demonti (2016)
This research aims to examine human resources, internal control, and utilization of information technology on the quality of local government reporting. This research object is the local government region of Klaten district, Sukoharjo, boyolali, and the town solo through financial services and asset management income areas. Sample in the study amount to 200 sample were employees of financial services and asset management income area in the district of Klaten, Sukoharjo, Boyolali, and the town Surakarta. The sample of using purposive sampling. Data analysis were regression linier berganda. The results of this study showed that the variables of human resources (HR), internal control (PI), the utilization of information technology (PTI) simultaneously affect the quality of reporting of local government to the level of significance of 0.000 <0.05.